Women’s Language in “500 Days Of Summer” Movie - Kadek Dwinata Satya Yoga; Ni Made Suwari Antari; Ni Ketut Sri Rahayuni (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
This undergraduate thesis was conducted to identify the women language feature and types of speech function used by Summer in the movie by using theory conducted from Robin Lakoff and Janet Holmes. The method that used in this undergraduate thesis is qualitative and quantitative research. The method that used to collect the data is Documentation method and note taking technique and for the used to analyzed the data is Qualitative and Quantitative method. To presented the data, the method that used is formal and informal method. The results of the data that has been found are eight out of ten features of woman language. Lexical hedges or fillers were the most used features by Summer (23%). There are found four out of six types of speech function. Referential function were the most used types by Summer (36%).